Um diagnóstico sobre a influência que os diferentes modelos de seleção exercem sobre a diferenciação de candidatos em concursos públicos - Raunheitti, Vivian Távora (2016)
The present work aims to evaluate the influence that different methods of selection exert over the differentiation of candidates in public examinations organized by FGV Projetos. Three stages were considered for this study: the objective written test, the discursive written test and the evaluation of titles. In the attempt towards deepening of public selection process, FGV Projetos has been formulating, in its exams, questions that require the necessary skills to perform a specific public function. In this sense, based on the obtained results, an individual and joint diagnosis of selection models currently applied were achieved The study also intends to be a guideline for the recruitment processes, establishing as a criterion of influence the weighted average of the grades of each stage of selection, the performance of one stage in relation to the other and the classification of the candidates on the final results. In order to achieve this, the candidates should undergo judicious evaluations, with different stages pertinent to the specifics of the position. The present work had a quali-quantitative nature, used a non-random sampling of the public examinations, realized by FGV Projects for the Administration area and adopted, as a data collection instrument, the documentary investigation of the opening announcements and the collection of secondary data of the results of 20 (twenty) selective processes executed and homologated between the years of 2013 and 2016. Finally, the socioeconomic and -demographic aspects of the candidates in comparison with their final position in the process were associated. The subjects of this study were those enrolled in the process who were present on the objective written test and / or the discursive written test, applying for Public Examinations for administrative areas, all of higher education level, segmented by the same field of knowledge.